2004
DOI: 10.4049/jimmunol.173.1.145
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Therapy of Murine Collagen-Induced Arthritis with Soluble T1/ST2

Abstract: Rheumatoid arthritis is characterized by chronic inflammatory infiltration of the synovium, leading to eventual cartilage and bone destruction. Previously, we have reported that soluble T1/ST2 (sST2), a member of the IL-1R gene family, inhibits LPS-induced macrophage proinflammatory cytokine production. In this study, we report the therapeutic effect of sST2-Fc in the murine model of collagen-induced arthritis. A short term administration of sST2-Fc fusion protein significantly attenuated disease severity comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(134 citation statements)
references
References 37 publications
4
127
2
1
Order By: Relevance
“…Increased serum levels of sST2 have been detected in a number of human diseases, including asthma and allergic airway inflammation, acute myocardial infarctions, and sepsis [10][11][12][13][14]. Although the biological significance for the increase in sST2 is not understood, several studies have demonstrated beneficial effects of sST2 treatment in animal models of diseases [2,4,6,15], suggesting that it may reduce inflammation. Intraperitoneal injection of IL-33 in mice resulted in splenomegaly, eosinophila and elevated serum IgE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased serum levels of sST2 have been detected in a number of human diseases, including asthma and allergic airway inflammation, acute myocardial infarctions, and sepsis [10][11][12][13][14]. Although the biological significance for the increase in sST2 is not understood, several studies have demonstrated beneficial effects of sST2 treatment in animal models of diseases [2,4,6,15], suggesting that it may reduce inflammation. Intraperitoneal injection of IL-33 in mice resulted in splenomegaly, eosinophila and elevated serum IgE.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that treatment of mice with a soluble form of ST2 (sST2) which can neutralize the function of IL-33, significantly attenuated established septic shock [5] and collagen-induced arthritis [6]. Recently, it has been reported that IL-33 injected intraperitoneally led to splenomegaly, eosinophilia and elevated serum IgE levels.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that sST2 could act as an anti-inflammatory mediator, through a mechanism that involves the inhibition of Toll-like receptor signaling by sequestration of MyD88 and Mal adapter proteins [45,46] or inhibition of I-κB degradation [47] resulting in down-regulation of NF-κB. In vitro and in vivo experiments have shown that sST2 protein or an ST2-fusion protein is able to attenuate the production of pro-inflammatory cytokines IL-1β, TNF-α, IL-6, and IL-12 [30,45,48]. In two mouse models of ischemia/reperfusion, pretreatment with an sST2-Fc fusion protein decreased the inflammatory response [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…4a). It has been previously reported that pre-treatment with sST2/Fc inhibits cytokine production induced by LPS in macrophages [15][16][17]. We thus examined whether sST2/Fc could also affect the response to LPS in BMMC.…”
Section: Il-33 Induces Il-6 Production By Bmmcmentioning
confidence: 99%